TEACHING ADULTS FOREIGN LANGUAGE, CHALLENGES AND SOLUTIONS - Ibragimova , Shahnoza Turgunovna (Innovative Development in Educational Activities, 2023)
In this article, we will explore some of the strategies, challenges and solutions in teaching adults foreign language. Methods like creating a positive learning environment, focusing on practical, real-world applications of the language, providing opportunities for adults, practice using the language in a safe and supportive environment, being patient and understanding are discussed. Solutions to challenges such as different learning styles and preferences, motivation, busy schedules and making mistakes are also proposed.